RANCANG BANGUN SISTEM PROTEKSI ARUS LEBIH MOTOR 3 FASA DENGAN TIMER START DAN TRIP - ., Andri Tukananto (Faculty of Engineering, Universitas Tanjungpura, 2015)
Abstract- Induction motor when turned on directly will pull the current 5 to 7 times the full load current. The Â current that Â beganÂ this Â great Â can Â resultÂ in Â a voltage drop on the line so that it will interfere with other devices connected on the same line. For large power motor starting current will also be greater, so for motor with power above 30 or 50 hp are not recommended to turned on the motor directly. Right now, in Siantan Diesel Power Plant using Thermal Overload to protect the overcurrent, therefore in this research is about â€Rancang Bangun Sistem Proteksi Arus Lebih Motor Induksi 3 Fasa Dengan Timer Start dan Tripâ€. This design started from the selected conditions of Â the Â motorÂ field Â and Â data Â in Â Siantan Diesel Power Plant. This result of design has result of start current meansurement up to 380A in less than 0,5 seconds, meanwhite the nominal current when its working after the start current is 77A. To achieve nominal currents that needed lestÂ than 3 Â seconds, because the setting on the timer start and trip is 3 second, if it exceeds the time limit setting then the circuit will trip. The current trip in the measurement result 2,6A with time tolerance setting less than 3 seconds that can be set on IC 555 through a trimpot. With the delay system, composed of the timer start and trip will reducer configuration overcurrent, all components such as Resistor, LM 741, Relay 12V DC and other expeted to control the current to the motor gradually Â in Â accordanceÂ with Â the Â desired Â setting. Thus motor starting problem and distraction from the induction motor 3 phase can be overcome. mengalami gangguan yaitu dari arus lebih yang dapat merusak motor tersebut. Berikut Â contoh Â permasalahan Â akibat Â gangguan Â pada motor induksi di lingkungan industri (PLTD Siantan): 1)Â Â Lifetime peralatan listrik atau mesin semakin menurun. 2)Â Â Seringnya terjadiÂ Â kasusÂ Â gulungan terbakar, kerusakan bearing pada motor Â induksi 3 fasa karena terjadinya arus lebih,dll. Â Permasalahan tersebut diharapkan akan teratasi selain menggunakan Thermal Overload Relay (TOR) yaituÂ denganÂ merancang dan Â membuat alat Â proteksi arus lebih motor induki 3 fasa dengan timer start dan trip. Dari pembuatan alat pengaman motor induksi 3 fasa ini diharapkan motor dapat bebas dari gangguan khususnya gangguan arus lebih. Â 2.Â Â Â Â MOTOR INDUKSI 3 FASA DAN PROTEKSI ARUS LEBIH A.Â Â Motor Induksi 3 fasa [1 â€“ 3] Â Konstruksi motor induksi secara detail terdiri atas dua bagian, yaitu: bagian stator dan bagian rotor. Stator adalah bagian motor yang diam terdiri : badan motor, inti stator, belitan stator, bearing dan terminal box. Bagian rotor adalah bagian motor yang berputar, terdiri atas rotor sangkar, poros rotor. Â Keywords ; Timer start, Timer trip, Overcurrent Â